2000
DOI: 10.2134/jeq2000.00472425002900050027x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Test Phosphorus and Clay Content Effects on Runoff Water Quality

Abstract: Dissolved phosphorus (P) in runoff increases with an increase in soil test P, but slopes found for this relationship vary by an order of magnitude. A difference in clay content contributes to this variation. Experiments were conducted on Ultisols of 5 and 32% clay by incorporating poultry (Gallus gallus domesticus) litter and triple superphosphate (TSP) to create a wide range in Mehlich 3‐extractable phosphorus (M3P). Mehlich 3 P increased similarly for the two sources with rate of P applied, but the increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 0 publications
9
70
0
Order By: Relevance
“…Several studies have shown that dissolved P (DP) concentrations in runoff were highly related to soil P levels that were determined using the agronomical soil tests Sharpley et al, 1994;Kleinman et al, 1999;Cox and Hendricks, 2000). Andraski and Bundy (2003) reported that agronomic soil P tests, that are already widely available, could provide an adequate indication of DP concentration in runoff, and that specialized environmental soil P tests were usually not necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that dissolved P (DP) concentrations in runoff were highly related to soil P levels that were determined using the agronomical soil tests Sharpley et al, 1994;Kleinman et al, 1999;Cox and Hendricks, 2000). Andraski and Bundy (2003) reported that agronomic soil P tests, that are already widely available, could provide an adequate indication of DP concentration in runoff, and that specialized environmental soil P tests were usually not necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The fate and transport of P in the soil environment has been shown to be responsive to a broad range of abiotic and biotic processes (Frossard et al,2000), including: soil test P (Cox and Hendricks, 2000;McDowell and Sharpley, 2001); landuse (Beauchemin et al, 1996); tillage (Kingery et al, 1996); soil mineralogy and particle size distribution (Cox and Hendricks, 2000); erosion ; manure application (Beauchemin et al, 1996;Kleinman et al, 1999; Published by Copernicus GmbH on behalf of the European Geosciences Union. 264 W. D. Hively et al: Phosphorus transport in an agricultural landscape Kleinman and Sharpley, 2003); grazing (Smith and Monaghan, 2003); plant uptake (Koopmans et al, 2004); P mass balance and soil accumulation (Cassell et al, 1989); soil moisture and hydrology (McDowell and Sharpley, 2002b); soil type (Needelman et al, 2004) and management (Ginting et al, 1998;Klatt et al, 2003;Sharpley and Kleinman, 2003); temperature and precipitation (Correll et al, 1999); sorption kinetics (Morel et al, 2000;Schoumans and Groenendijk, 2000); and preferential flow and soil structure (Akhtar et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that soil texture, soil pH, soil genesis as related to mineralogy, Fe and Al oxyhydroxides, soil organic matter accumulation, as well as depth of water table could influence soil P sorption capacity, and quality of runoff and drainage water (Juo and Ellis 1968;Laverdière and Karam 1984;Giroux and Tran 1985;Breeuwsma and Silva 1992;Breeuwsma and Reijerink 1993;Simard et al 1994Simard et al , 2000Sharpley 1995;Sims et al 1998;Djodjic et al 1999;Cox and Hendricks 2000;Leclerc et al 2001). A useful environmental soil test P (STP) for assessing P accumulation should extract all or a representative amount of the P fraction in soils that is susceptible to surface runoff, leaching, or dissolution from eroded sediments, and be rapid, accurate, inexpensive and reliable (Moore et al 1998).…”
mentioning
confidence: 99%